Marketing Margins and Efficiency of Cooking Banana Retail Trade in Kampala City, Uganda - Kalule, Stephen W.; Kyanjo, Joseph L. (International Journal of Sales and Marketing, 2013)
Cooking bananas like many other food crops in Uganda have experienced consumer price hike threatening poor and urban consumers’ dietary diversity and food security. Unfortunately, little research attention has been paid to the demand side of this stapple’s supply chain and there is hardly any study that has examined its marketing system performance. Using a sample of 80 representative retail traders, the study examined marketing margins and efficiency of small and big size banana bunches. Results revealed that the banana retail trade was highly inefficient. However, the inefficiency was more felt in trading small size banana bunches than big ones. OLS results on the other hand showed that marketing efficiency was significantly reduced by marketing costs though significantly improved by the scale of operation. The study recommended that provision of policy incentives such as low interest credit to retail traders as way of encouraging business expansion and backward market integration.
Keywords: TVECM; MAAIF; Banana Bunches; Marketing Margins